2018
DOI: 10.1149/2.1301802jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Role of Trivalent Chromium on the Anti-Corrosion Properties of a TCP Conversion Coating on Aluminum Alloy 2024-T3

Abstract: Electrochemical methods were used to study the role of Cr(III) on the anti-corrosion behavior of a trivalent chromium process conversion coating on AA2024-T3. The same conversion coating was investigated with and without Cr(III) added to the bath. Polarization curves (naturally-aerated 0.5 M Na 2 SO 4 + 0.1% NaCl) revealed similar anodic current suppression by both coatings. Cathodic currents were suppressed more by the coating with Cr(III). Rotating disk voltammetric data revealed that cathodic currents for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
3
25
0
1
Order By: Relevance
“…In summary, both EAD and DC techniques enable an uniform film deposition [ 19 , 53 ]. It has been observed that, despite the ZrO 2 coating formation is supposedly favored by the application of low cathodic potential in electro-assisted method, the correct mechanism is probably a combination of both a chemisorption process and the electro-assisted one happening simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, both EAD and DC techniques enable an uniform film deposition [ 19 , 53 ]. It has been observed that, despite the ZrO 2 coating formation is supposedly favored by the application of low cathodic potential in electro-assisted method, the correct mechanism is probably a combination of both a chemisorption process and the electro-assisted one happening simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Coating technology doped with specific inhibitors combines the advantages of both and has broad application prospects. Tsai et al [78], and Shruthi et al [79], respectively, conducted experiments on the anticorrosion coating technology of aviation aluminum alloy. Marshall et al [80], through finite element simulation, calculated relevant parameters after the coupling of coated aluminum alloy and stainless steel.…”
Section: Research In the Field Of Corrosion Inhibitionmentioning
confidence: 99%
“…2630) Shruthi and Swain evaluated the effect of trivalent chromium treatment on the oxygen reduction reaction rate on AA2024-T3. 26) They reported that the oxygen reduction reaction on the Cu-rich IMPs was extremely suppressed by the treatment. For Al alloys, Zrbased conversion treatments have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%